Diversity and biogeography of land snails (Mollusca, Gastropoda) in the limestone hills of Perak, Peninsular Malaysia - Foon, Junn Kitt; Clements, Gopalasamy Reuben *; Liew, Thor Seng (Pensoft Publishers, 2017)
Limestone hills are now gaining global conservation attention as hotspots for short-range endemic species. Levels of land snail endemism can be high at limestone hills, especially at hill clusters that are geographically isolated. In the State of Perak, Peninsular Malaysia, limestone hills have been opportunistically surveyed for land snails in the past, but the majority have yet to be surveyed. To address this knowledge gap, we systematically surveyed the terrestrial malacofauna of 12 limestone hills that, based on our opinion, are a representation of the limestone land snail assemblages within the State. Our inventory yielded high sampling completeness (>85%). We found 122 species of land snails, of which 34 species were unique to one of the surveyed hills. We identified 30 species that are potentially new to science. The number of land snail species recorded at each hill ranged between 39 and 63 species. Four of the sampled limestone hills namely, Prk 01 G. Tempurung, Prk 55 G. Pondok, Prk 47 Kanthan, and Prk 64 Bt Kepala Gajah, have high levels of species richness and unique species, representing 91% of the total species recorded in this study. We identified two clusters of limestone hills in central Perak with distinct differences in land snail species composition – a northern hill cluster on elevated granite bedrock and southern hill cluster in a low-lying valley surrounded by alluvial soils. As limestone hills continue to be quarried to meet the cement demand, the four identified limestone hills, along with other hills from the two clusters, warrant urgent conservation attention in order to maintain high species diversity within Perak’s terrestrial malacofauna.